Repurposing the Suzuki frame: a novel approach for neglected proximal interphalangeal joint intra-articular fracture management - Patidar, Sunil; Kayathwal, Ankit Kumar; Raghu, Aashish (International Journal of Research in Orthopaedics, 2025)
Neglected intra-articular fractures of the proximal interphalangeal (PIP) joint pose significant challenges due to joint stiffness, malalignment, and compromised function. Traditional management often yields suboptimal outcomes, especially in delayed presentations. We report a novel application of the Suzuki frame-conventionally used for distal interphalangeal (DIP) joint injuries-in the treatment of a neglected PIP joint intra-articular fracture in a young male patient. The fracture was managed using a dynamic external fixator constructed with K-wires and rubber bands, allowing controlled distraction and early mobilization. A modified Suzuki frame was applied across the PIP joint, achieving stable fixation and facilitating gradual distraction. The construct enabled early range-of-motion exercises while maintaining reduction. Radiological and functional outcomes were assessed over a 12-week follow-up. The patient demonstrated excellent clinical recovery, with restoration of joint alignment, pain-free range of motion, and return to pre-injury activity levels. Radiographs confirmed satisfactory fracture healing and joint congruity. This case highlights the versatility of the Suzuki frame in managing complex PIP joint injuries, especially in neglected cases. The technique offers a minimally invasive, cost-effective, and function-preserving alternative that warrants further exploration in larger cohorts.